Bactericidal Effect and Mechanism of Polyhexamethylene Biguanide (PHMB) on Pathogenic Bacteria in Marine Aquaculture - Lanting Wu; Chunyuan Wang; Yingeng Wang; Yongxiang Yu; Zheng Zhang; Cuiping Ma; Xiaojun Rong; Ling Chen; Meijie Liao; Yapeng Yang (Biology)
Guanidine disinfectants are cationic polymers recognized for their effective sterilization properties and their ability to prevent bacterial resistance. As a result, they are widely utilized in medical, healthcare, household, and animal husbandry settings. However, the bactericidal effects and mechanisms of guanidine in marine aquaculture systems remain unclear due to the polymeric nature of guanidine ions and the complexity of marine environments. The inhibitory effects and bactericidal mechanisms of polyhexamethylene biguanide (PHMB) on key pathogens and probiotics are examined in this study. It was shown that PHMB had inhibitory effects on Vibrio parahaemolyticus (VP), Photobacterium damselae subsp. damselae (PDD), Bacillus subtilis (BS), Escherichia coli (EPEC), and Staphylococcus aureus (SAU), with minimum inhibitory concentrations (MICs) ranging from 3.91 to 125.0 µg/mL, and minimum bactericidal concentrations (MBCs) from 15.63 to 250.0 µg/mL. A stronger bactericidal effect of PHMB on marine bacteria compared to EPEC and SAU was exhibited. It was shown in ion interference experiments that the addition of calcium ions reduced the bactericidal effectiveness of PHMB against VP and PDD by 87.73% and 53.35%, respectively. At a PHMB concentration of 62.50 µg/mL, minor changes in cell surface potential energy (CSPE) were exhibited by Gram-positive bacteria (SAU and BS), while more significant alterations were shown by Gram-negative pathogens. It was revealed by propidium iodide staining and scanning electron microscopy (SEM) analysis that the bacterial cell membrane was directly disrupted by PHMB. DNA and RNA release analysis further revealed that following PHMB treatment, changes in membrane permeability were exhibited by Gram-negative pathogens, with a significant increase in extracellular DNA content as PHMB concentration increased. No such effect was observed in Gram-positive bacteria. Additional evidence was provided by the findings that PHMB effectively inhibits bacterial pathogens in mariculture systems, with a significantly stronger inhibitory effect on Gram-negative pathogens than on Gram-positive bacteria. These results indicated that PHMB could serve as a new antimicrobial agent in mariculture.